Quantum-secured Enterprise Mobility: Benefits of Integrating Abstracted Mobile Applications with QKE and VINs - Mazza, Anthony (Transactions on Engineering and Computing Sciences, 2025)
The convergence of enterprise mobility, quantum cryptography, and virtual invisible network technologies presents new opportunities for secure communications, albeit with complex integration challenges. This analysis explores the transformative impact of quantum key encryption (QKE) on modern cryptographic systems, platforming an examination of the benefits and technical feasibility of combining a single, abstracted mobile application that houses unified communication functions with quantum key encryption, deployed over virtual invisible networks (VINs). While RSA and elliptic curve cryptography (ECC) have served reliably for decades, their impending obsolescence necessitates urgent investment in quantum-safe infrastructure. The analysis draws on contemporary peer-reviewed research, industry standards, and technical implementations to evaluate security enhancements, operational gains, and deployment challenges. Key findings highlight the security advantages of quantum-resistant encryption, network obfuscation, and unified enterprise communications, while identifying critical challenges in scalability, implementation complexity, and resource requirements. Recommendations for staged deployment, hybrid security models, and standardized integration frameworks are presented to facilitate the practical adoption of these emerging technologies. Through a synthesis of contemporary research, the paper argues that quantum-resistant cryptographic protocols must be urgently developed and adopted to preserve information security in the quantum computing era.